Digital Governance-Informed Instructional Design Framework for Madrasah Education: A Systematic Literature Review - Muslikun Muslikun; Theresia Trisanti; Rusmawan Wahyu Anggoro; Efraim Ferdinan Giri; A. Umar (CV FOUNDAE, 2026)
The current era of modern Madrasah (Islamic schools) mandates their capacity to show not only effective learning outcomes but also their performance in public accountability aligned with digital governance. Nevertheless, the process of administrative digitization and instructional processes are conducted separately, leaving performance management scattered across these two areas. The present study intends to come up with an integrated conceptual framework that can effectively combine the concepts of Digital Governance (DG) and Instruction Design (ID). Using a Systematic Literature Review methodology (from 2015 to 2025) and Conceptual Design-Based Research approach, the study made use of a Boolean search string containing key terms like (”Digital Governance